Effects of Technological Change on the Labor Market in Mexico: An Analysis of Autoregressive Vectors for the Manufacturing Sector, 2005-2021 (Global Journal of Human-Social Science, 2024)
This paper presents an analysis of the effect of technological change on the labor market in the manufacturing sector in Mexico, in the period 2005-2021. Based on the human capital theory and the biased technological change approach, we study whether the manufacturing labor market presents a skills-biased technological change based on the correspondence between groups of low-and high-skilled workers in relation to the distribution of tasks: abstract, manual and routine. The objective is to show, through separate equations, whether the supply of skilled workers is related to abstract tasks and, on the other hand, whether unskilled work is assigned to manual and routine tasks. Through a VAR analysis, in general, consistent evidence is shown that the future of the supply of skilled labor is explained by abstract tasks..
Keywords: labor market; technological change; skills; vector autoregressive analysis